Description of a new species of the black fly subgenus Simulium (Ectemnaspis) from the Andes of Ecuador (Diptera: Simuliidae) - Coscarón, Sixto (1989)
Simulium (Ectemnaspis) pautense sp. n. was described based on female, male, pupal and larval specimens collected in small streams of Andean region in Ecuador. This new species is close to S. (E.) gabaldoni Ramirez Perez from Venezuela by having the 6-filamented pupal gills, but differs in the female from the latter species by lacking denticles in the cibarium and by the coloration of the legs.